THE INFLUENCE OF CUSTOMER SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION AND ITS IMPLICATION ON LOYALTY: A SURVEY ON MICE CUSTOMERS IN HOTELS - Suresh Kumar; Jessica Samtani (FIRM Journal of Management Studies, 2021)
This research was conducted to determine the Influence of Customer Service Quality towards Customer Satisfaction and its implication on Loyalty among MICE Customers in Hotels surrounding Bekasi. For service quality, instead of applying the famous SERVQUAL, this study uses the newly build service quality for hotel industry, HOLSERV.  Quantitative data analysis was applied to test the relationship among the variables. Prior to that, data were tested for its validity and reliability. Customers of hotels surrounding Bekasi were taken as the respondents with the help of hotel managers who participated in the study. Participants were taken not only those experiencing MICE but also from the employee category assuming the degree of exposure to MICE much higher than students. Structural equation modelling was applied to test the influencing factors among the variables since it has better details in results compare to multiple regression technique. The result shows all the variables in HOLSERV have a significant influence on Customer Satisfaction which leads to Customer loyalty. In addition, customer satisfaction itself has proven to be significant to loyalty.